Effect of differential duration of androgen treatment on growth of Nile tilapia under Indian condition - Banerjee, Suman Bhusan Chakraborty, Samir (Recent Research in Science and Technology, 2009)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 1pt; border-left: medium none; padding-top: 1pt; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt; mso-border-bottom-alt: solid windowtext .5pt;"><p class="MsoNormal" style="margin: 0in 0in 0pt; text-align: justify; mso-border-top-alt: solid windowtext .5pt; mso-border-bottom-alt: solid windowtext .5pt; mso-padding-alt: 1.0pt 0in 1.0pt 0in; padding: 0in;">Little is known about the effect of differential duration of androgen treatment on growth performance of Oreochromis niloticus in India. In this study, 3 days old juveniles of tilapia were fed with 17ÃŽÂ±-methyltestosterone treated diet for three different duration regimes: 0 days (control), 30 days (30 days treatment) and 180 days (throughout treatment). After six months of culture, different growth parameters like body weight, length, depth, daily weight gain (DWG), specific growth rate (SGR) and proximate body composition were analyzed. The serum testosterone concentrations of the fish were measured from the 3rd month of culture. It was found that both the 30 days treated and throughout treated categories yielded significantly higher weight, length, depth, DWG, SGR and protein content compared to the control fish. But, there was no significant difference in growth parameters among the two hormone treated groups. Achievement of an optimum saturation level of hormone activity after the application of a particular titre of testosterone may attribute to such trend in growth pattern. The serum testosterone concentration of the 30 days treated fish at the end of culture period is similar to that of the control males. This can validate the human consumption of the 30 days treated tilapia rather than throughout treated ones that have 2 times more testosterone concentration at the same time. Thus, dietary androgen treatment for the first month of culture followed by rearing with control diet can be regarded as the ideal method for sustainable augmented fish production in India.